The discreditation of girdite. (1st October 2017) - Kampf, Anthony; Mills, Stuart; Rumsey, Mike
Girdite, a mineral described by Williams in 1979 from the Grand Central mine, Tombstone, Cochise County, Arizona, USA, has been re-examined by powder X-ray diffraction, single-crystal X-ray diffraction and electron microprobe. Type material from The Natural History Museum, London and the United States National Museum of Natural History (Smithsonian Institution) was examined. The original description of girdite is shown to have been based upon data obtained from at least two and possibly three different phases, one corresponding to ottoite and another probably corresponding to oboyerite, although the latter itself appears to be a mixture. The discreditation of girdite as a valid mineral species has been approved by the IMA-CNMNC, Proposal 16-G.